2018
DOI: 10.1038/s41536-018-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in clinical trials for articular cartilage repair by cell therapy

Abstract: Focal and degenerative lesions of articular cartilage greatly reduce the patient’s quality of life. Various therapies including surgical treatment have been developed, but a definitive therapy is not yet known. Several cell therapy products have already been developed and are available in the market. In this study, we examined the clinical research trends related to cell therapy products in the cartilage repair field based on data obtained from the ClinicalTrial.gov website. Although this website does not prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 20 publications
0
78
0
Order By: Relevance
“…Limitations with ACh-based therapies for cartilage repair are driving investment into therapies that utilize BMSCs or other cell populations [29]. The most commonly evaluated alternative cell populations are bone marrow-derived cells (31%, including BMSCs) [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations with ACh-based therapies for cartilage repair are driving investment into therapies that utilize BMSCs or other cell populations [29]. The most commonly evaluated alternative cell populations are bone marrow-derived cells (31%, including BMSCs) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations with ACh-based therapies for cartilage repair are driving investment into therapies that utilize BMSCs or other cell populations [29]. The most commonly evaluated alternative cell populations are bone marrow-derived cells (31%, including BMSCs) [29]. However, the progression of prospective therapies using bone marrow-derived cells to phase III trials is low (3.2% [29]), and no BMSC cartilage repair therapies have attained FDA approval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A commercial product CARTISTEM that is manufactured with Hyaluronic acid and allogenic MSCs that is in clinical trials for articular cartilage defects (NCT01733186 and NCT01626677). The most common cell‐based treatment for chondral defects in humans is currently the autologous chondrocyte transplantation, both alone or placed on natural scaffolds . However, that trend might shift if the results of the clinical studies confirm the same potential of biomaterial‐delivered stem cells as the preclinical studies have shown.…”
Section: Applications Of Advanced Biomaterials For Stem Cell Deliverymentioning
confidence: 99%
“…Furthermore, clinical trials were suggested to assess matrix efficacy and safety. These approaches are of the particular interest especially in reconstructive surgery in case of regeneration of soft tissues damages and wound healing [38,39,40].…”
Section: а B Cmentioning
confidence: 99%